2015
DOI: 10.9724/kfcs.2015.31.5.534
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Sensory Evaluation of Tenebrio molitor Larvae Cooked by Various Cooking Methods

Abstract: Recently, the Tenebrio molitor larva was recognized as a novel food ingredient by the Ministry of Food and Drug Safety in Korea. Accordingly, we investigated its physical and sensory characteristics to establish the cooking conditions that may increase the demand of T. molitor larvae as a food. In this study, T. molitor larvae were cooked by various methods such as hot air dry, oven-broil, roast, pan fry, deep fry, boil, steam, and by microwave. In the physical evaluation of texture, the hardness and fracturab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In a previous study, Baek et al . () reported that the textures of boiled and steamed mealworms were soft and juicy because the moisture content was high, whereas the textures of those prepared by dry heat processing methods, such as freeze drying, hot air drying, oven broiling, roasting, pan frying, deep frying, and microwaving, were crispy with a savory flavor (Baek et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, Baek et al . () reported that the textures of boiled and steamed mealworms were soft and juicy because the moisture content was high, whereas the textures of those prepared by dry heat processing methods, such as freeze drying, hot air drying, oven broiling, roasting, pan frying, deep frying, and microwaving, were crispy with a savory flavor (Baek et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…() reported that the textures of boiled and steamed mealworms were soft and juicy because the moisture content was high, whereas the textures of those prepared by dry heat processing methods, such as freeze drying, hot air drying, oven broiling, roasting, pan frying, deep frying, and microwaving, were crispy with a savory flavor (Baek et al . ). Therefore, it may be useful to utilize dried T. molitor larvae, which have a good taste and flavor, crispy texture, and high nutrition density, as a novel food source with good taste and nutrient content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations